1997
DOI: 10.1016/s0009-9236(97)90034-5
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of lovastatin, but not pravastatin, in the blood of cyclosporine-treated kidney graft patients after multiple doses*

Abstract: In contrast to lovastatin, pravastatin did not accumulate over the study period, which is probably one of the reasons rhabdomyolysis has been reported in lovastatin-treated but not pravastatin-treated transplant patients receiving cyclosporine immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 23 publications
7
80
0
Order By: Relevance
“…Because pravastatin is not metabolized, this increase is likely to be attributed to the inhibition of hepatic uptake transporters. These results confirmed results of an earlier study performed in patients who underwent kidney transplantation and are receiving pravastatin or lovastatin together with CsA [Table 3 (Olbricht et al, 1997)]. It is noteworthy that, in this study, it was demonstrated that pravastatin coadministered with CsA did not accumulate over the study period, even if the AUC was 5-fold higher than values reported in the absence of CsA (AUC for single dose at day one: 249 mg  h/ml, AUC for multiple doses after 28 days: 241 mg  h/ml), whereas lovastatin accumulated over time in CsA-treated patients (AUC for single dose at day one: 243 mg  h/ml, AUC for multiple doses after 28 days: 459 mg  h/ml).…”
Section: Drug-drug Interactionssupporting
confidence: 90%
“…Because pravastatin is not metabolized, this increase is likely to be attributed to the inhibition of hepatic uptake transporters. These results confirmed results of an earlier study performed in patients who underwent kidney transplantation and are receiving pravastatin or lovastatin together with CsA [Table 3 (Olbricht et al, 1997)]. It is noteworthy that, in this study, it was demonstrated that pravastatin coadministered with CsA did not accumulate over the study period, even if the AUC was 5-fold higher than values reported in the absence of CsA (AUC for single dose at day one: 249 mg  h/ml, AUC for multiple doses after 28 days: 241 mg  h/ml), whereas lovastatin accumulated over time in CsA-treated patients (AUC for single dose at day one: 243 mg  h/ml, AUC for multiple doses after 28 days: 459 mg  h/ml).…”
Section: Drug-drug Interactionssupporting
confidence: 90%
“…Cyclosporine, for instance, inhibited OATP1B1-and OATP1B3-mediated drug uptake in vitro (Treiber et al, 2007). Thus, it has been observed in humans that coadministration of the OATP1B1 and OATP1B3 substrate pravastatin with cyclosporine increased the plasma concentrations of pravastatin (Regazzi et al, 1993;Olbricht et al, 1997;Park et al, 2002;Hedman et al, 2004). Because pravastatin is not metabolized to a significant extent (Jacobsen et al, 1999), inhibition of OATP1B1-and OATP1B3-mediated pravastatin uptake may be one relevant molecular mechanism behind this observed drug-drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This is because lovastatin is metabolized by CYP3A4, whereas the major pravastatin metabolites are generated by non-CYPdependent processes. 38,39) The AUC of bosentan nearly doubled after seven days of co-administration with cyclosporine, but the AUC values of cyclosporine were the same for doses with and without bosentan. 40) Bosentan is metabolized by CYP3A4 and CYP2C9, but it also induces these CYPs.…”
Section: Ešect Of Cyclosporine and Tacrolimus On Cyp3a4-mediated Nimentioning
confidence: 98%